Folate Reductase and Specific Dihydrofolate Reductase Activities of the Amethopterin-Sensitive Streptococcus faecium var. durans - Albrecht, Alberta M. (1969)
Preliminary evidence is presented that indicates that the dihydrofolate reductase activity of amethopterin-sensitive Streptococcus faecium var. durans ATCC 8043 is separable into two dihydrofolate reductases, one of which also reduces folate.